2013
DOI: 10.1111/vox.12093
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the current 12‐month deferral for male‐to‐male sex in Australia

Abstract: Our study confirms high compliance (>99·7%) to the 12-month deferral for male-to-male sex in Australia providing reassuring evidence for the efficacy of the screening question. Issues of 'privacy' and 'discomfort' associated with disclosure suggest the use of validated audio computer-assisted structured interview as a possible option for improving compliance with the donor questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
53
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 26 publications
14
53
2
Order By: Relevance
“…Donors could think that answering truthfully has consequences for them being a donor or do not feel comfortable to report their sexual behavior during an online survey. However, our response rate was adequate (comparable or higher than other compliance studies [16][17][18][19] for an online survey about such a sensitive topic, and the overall noncompliance rate was comparable to other countries.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Donors could think that answering truthfully has consequences for them being a donor or do not feel comfortable to report their sexual behavior during an online survey. However, our response rate was adequate (comparable or higher than other compliance studies [16][17][18][19] for an online survey about such a sensitive topic, and the overall noncompliance rate was comparable to other countries.…”
Section: Discussionsupporting
confidence: 58%
“…Privacy reasons have also been found to play a role in other compliance studies of MSM. 13, 16 We also found that MSM in general perceive the policy more as discriminating compared to compliers and women.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We conducted a large, online, anonymous national survey to estimate the prevalence of, and factors associated with, noncompliance with the existing deferrals for IDU; sex with an injecting drug user; MSM; and females with MSM partners, sex worker activity or contact, and new sexual partner from a HHPC, among TTI test–negative Australian donors. Using a subset of data from this survey we have previously reported results on noncompliance with our MSM deferral . Here we report data associated with the other high‐risk sexual and nonsexual deferral criteria for which information was collected in the survey.…”
mentioning
confidence: 99%
“…Still, a varying percentage of donors are identified with HIV and HCV infections with deferrable risks that were not detected or reported in the donor selection process [1,5,13,14]. Comparison of risk factors among infected blood donors and infected individuals from the general population is only rarely used to assess the effectiveness of blood donor selection procedures.…”
Section: Discussionmentioning
confidence: 99%